Avaliação das propriedades mecânicas das placas cimentícias e do comportamento da ligação entre as placas cimentícias e o reticulado de aço do sistema light steel framing - Ana Carolina Saraiva Cardoso (2019)
This research presents the results of a theoretical-experimental study of the connection behavior of cement board with the cold formed steel profiles of the Light Steel Framing (LSF) construction system. The cement board is used as a sheathing board in this structural system. However, because it has considerable mechanical resistance, it will be evaluated through tests to verify its contribution in the structural system. Especially in the shear wall subsystem, the sheeting plates attached to the profiles can help resist lateral forces and excessive displacements. Three-point flexural tests and compression tests were performed to characterize the plates. And sliding assays to evaluate the bond between plate and metallic crosslinking. For the latter, three specimen models were constructed to evaluate the behavior of plate edge and plate center screws in a shear wall. The autoclaved cement board reinforced with cellulose fibres of 10mm and 12mm thickness were classified as class B, category 2 with strength at flexion greater than 7MPa and less than 10MPa. With respect to the compression tests, it was concluded that they are better suited for dosage cement board components. From the 48 series of push-tests carried out, it was concluded that the parameters that influenced the models uniformly were the PLC thickness and the steel profile thickness. Thus, the lower the thickness of the steel and the board, the lower the Pmax value and the higher rigidity tends to be. The variables board cutting direction and axial spacing between the screws were not conclusive. Moreover, according to the uniform fabrication process of the cement board, it does not justify classifying or differentiating the boards in longitudinal and transverse. The maximum force supported by each screw connection was approximately equal for the two axial spacings used: 150mm and 300mm.